2020
DOI: 10.3390/children7070076
|View full text |Cite
|
Sign up to set email alerts
|

“I Wasn’t Sure What It Meant to Be Honest”—Formative Research Towards a Physical Literacy Intervention for Preschoolers

Abstract: Physical literacy (PL) as a concept is important in developing lifelong physical activity; however, there is little research exploring how PL can be developed during the preschool years. This two-phase qualitative study sought the insights of academics/expert practitioners and preschool staff towards PL in order to inform the design of future preschool PL interventions. Phase One comprised of nine semi-structured interviews with experts in the field of children’s physical activity and/or PL. Interview topics i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 55 publications
0
16
0
1
Order By: Relevance
“…P1, expert (Participant 1 Expert Focus Group 1). For profile inclusion, the threshold was a minimum of 25% consensus within a theme and themes not reaching consensus were reported within the narrative (Foulkes et al 2020). For transparency, the total number and percentage of individual participants who spoke in relation to a theme is therefore presented.…”
Section: Discussionmentioning
confidence: 99%
“…P1, expert (Participant 1 Expert Focus Group 1). For profile inclusion, the threshold was a minimum of 25% consensus within a theme and themes not reaching consensus were reported within the narrative (Foulkes et al 2020). For transparency, the total number and percentage of individual participants who spoke in relation to a theme is therefore presented.…”
Section: Discussionmentioning
confidence: 99%
“…The environmental resources available to each child to foster FMS could be enhanced through changing the design of play spaces within the recess playground to include natural landscapes and features (e.g., forested areas with trees and shrubs, rocks, water, sand, uneven ground, slopes) [56,74,75], as well as increasing the volume and range of loose parts and fixed equipment [60][61][62]. The role of preschool educators should be to encourage and offer possibilities for active play while fully respecting child agency [68][69][70]. Nevertheless, due to the narrow evidence base, more research exploring how to maximize affordances for young children to develop FMS during preschool recess periods is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, gender differences in play group compositions may influence FMS. Previous studies have also shown how childcare educators’ education, attitudes, beliefs, behaviors, and practices may influence preschool children’s physical activity, FMS, and physical literacy [ 68 , 69 , 70 ]. Therefore, examining if and how teacher attitudes and practices in relation to play behaviors and FMS and how teacher interactions with children during recess affect FMS competence could be an interesting area for future study.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Phase 1 was based on previous studies conducting formative research to explore educators' perceptions on physical activity intervention programs for preschool children [38] as well as their perspectives on technology use [39]. It showed that both parents and educators have a preference of short online programs with duration between 10-30 min, and to be contacted weekly via email.…”
Section: Discussionmentioning
confidence: 99%